Multiple languages in childhood: shared protagonism between adults and children in children's education contexts - Martins Filho, Altino José (2022)
The social relationships engendered within an educational institution are woven by many relationships and different shades and with this understanding the objective of this work is to present some analytical and propositional considerations about the multiple languages of young children. It starts from a theoretical and methodological anchorage that dialogues with cultural pedagogies, social constructionism, interpretive science, hermeneutics and phenomenology. It is understood that it is necessary to discover the complexity of childhood, to get to know the children, that is, for the problematization of childhood experiences. We believe that children among themselves and with adults are not only socialized, but produce innovative processes and genuine forms of socialization, leading a way of being and being in the world beyond our adult-centeredness. Therefore, we have to know the grammar of children in their multiple languages. In this sense, we affirm the importance of the intensity of relationships through the bias of shared protagonism.